Evolution of Physical Therapy Education in China and Use of Simulation-based Learning to Maximize Clinical Placement Outcomes - Alice Y M JONES; Margot A SKINNER; Elizabeth DEAN (康复学报)
Objective:The purpose of this article is to describe the evolution of the profession of physical therapy and physical therapy entry level education in China, with specific attention to the role of simulation-based learning(SBL)experiences in preparing students for clinical placements.Methods:With respect to their education, physical therapy students, like medical students, require a structured clinical education programme to ensure professional competence on graduation. For many years, SBL has been the preferred mode of teaching and learning in medical, engineering, and aviation professions. Use of SBL as a mode of teaching and learning of clinical competencies in physical therapy program has also emerged.Results:This article discusses the advantages of adopting SBL in physical therapy entry level education, particularly the use of standardized patients in the form of actors, as a core educational component to prepare students for their clinical placements.Conclusion:We propose that SBL be adopted by physical therapy programs across China to maximize the clinical placement experiences for students.